Fatigue and Vibration Parameters Improvement of Steel DIN 41Cr4 by Ultrasonic Shock Peening Treatment - Mahmood, Zeina Shaker; Chiad, Jumaa Salman (Al-Nahrain Journal for Engineering Sciences, 2019)
The effects of the ultrasonic peening treatment (UPT) on the rotating bending fatigue behavior and the behavior of the vibrations of alloy steel DIN 41Cr4 were studied. Hardness test, Tensile test, Constant amplitude fatigue tests, and the vibrations measurements have been carried out on the specimens. Also, the fracture surface was examined and analyzed by a Scanning Electron Microscope (SEM). The results of the investigations, e.g. stress to number of cycles to failure (S-N) curves, fatigue strength improvement factor was 7%. The decreasing percentage of maximum Fast Fourier Transform (FFT) acceleration of the ultrasonic peened condition compared to the untreated conditions was 45%.